1999
DOI: 10.1177/002204269902900215
|View full text |Cite
|
Sign up to set email alerts
|

Heroin Sniffing as Self-Regulation among Injecting and Non-Injecting Heroin Users

Abstract: This paper examines sniffing as a mode of administration among three subgroups who sniff heroin: those who had never injected. those who were also injecting. and those who had ceased injection. Modified life-history interviews were conducted in 1994 with 26 people currently sniffing but not injecting, recruited in street-based settings in conjunction with an ongoing study of risk behavior and seroprevalence among drug injectors. These were supplemented by survey interviews and brief open-ended interviews with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 19 publications
5
25
0
1
Order By: Relevance
“…32 However, other studies have suggested that the level of social integration of drug users in society may influence their likelihood of injecting drugs. 45,46 Our finding supports this observation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…32 However, other studies have suggested that the level of social integration of drug users in society may influence their likelihood of injecting drugs. 45,46 Our finding supports this observation.…”
Section: Discussionsupporting
confidence: 87%
“…Although a first episode of drug injection does not necessarily mean that injection will become a regular route of drug administration, 7,18,45 initiation to injection is of major concern. Previous studies have suggested the existence of a hierarchy of dependence, with the greatest risk being associated with injecting, and that once a transition has been made to injecting, it tends to be maintained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research supports the argument that knowledge of and attitudes toward injection and the risk of AIDS are related to the transition to injection. 26,27 Hypothesis 3: Feature a higher degree of social marginalization from basic social institutions as measured by residential stability, educational achievement, and marital status. Social integration into or marginalization from major institutions of a society, such as housing, education, and family, may influence whether transition to injection occurs.…”
Section: Introductionmentioning
confidence: 99%
“…This same research has also identified having drug and sexual networks that include injectors as factors associated with transitioning. Furthermore, individual susceptibility such as personal traumatic events, fear of HIV/AIDS, not being afraid of needles and attitudes about injectors have been identified as important risks for making a transition (Bravo, Barrio, & de la Fuente, 2003;Casriel, Des Jarlais, Rodriguez, Friedman, & Khurl, 1990;Neaigus, Atillasoy, & Friedman, 1998;Sotheran, Goldsmith, Blasco, & Friedman, 1999).…”
Section: Introductionmentioning
confidence: 99%